2011
DOI: 10.1089/pho.2010.2856
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Violet Light Emitting Diode (LED) Irradiation Immediately Controls Socket Bleeding Following Tooth Extraction; Clinical and Electron Microscopic Observations

Abstract: Blue-violet LED irradiation of bleeding sockets caused immediate clot formation and hemostasis. This procedure was safe and reliable and showed no adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The examination group showed almost immediate bleeding stop after applying LED light, compared to the control group. These findings are very similar to the findings from author Isao Ishikawa et al, which tested the effects of LED on postoperative bleeding in oral surgery [ 11 ]. The duration of the irradiation needed to stop the bleeding in our study was also similar to his results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The examination group showed almost immediate bleeding stop after applying LED light, compared to the control group. These findings are very similar to the findings from author Isao Ishikawa et al, which tested the effects of LED on postoperative bleeding in oral surgery [ 11 ]. The duration of the irradiation needed to stop the bleeding in our study was also similar to his results.…”
Section: Discussionsupporting
confidence: 91%
“…The first phase consists of heating effects, followed by formation of spherocytes and met-haemoglobin. Finally, extended coagulum formation happens due to spherocyte rupture [ 11 ]. Thermal damage and carbonisation of the underlying soft and hard tissues could be possible complications after laser irradiation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These devices are more compact and portable and considerably less expensive compared to lasers (Takasaki et al 2009). Another advantage of LED is that its irradiation is less harmful to the eyes than laser irradiation (Ishikawa et al 2011). Previous in vitro study showed that LED-based PAD could effectively reduce the inflammatory response of macrophages to Porphyromonas gingivalis lipopolysaccharide adherent to titanium surface (Giannelli et al 2011).…”
mentioning
confidence: 99%